The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/2013jd020914
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and applications of NASA ozone data products derived from Aura OMI/MLS satellite measurements in context of the GMI chemical transport model

Abstract: Measurements from the Ozone Monitoring Instrument (OMI) and Microwave Limb Sounder (MLS), both on board the Aura spacecraft, have been used to produce daily global maps of column and profile ozone since August 2004. Here we compare and evaluate three strategies to obtain daily maps of tropospheric and stratospheric ozone from OMI and MLS measurements: trajectory mapping, direct profile retrieval, and data assimilation. Evaluation is based on an assessment that includes validation using ozonesondes and comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 74 publications
4
44
0
Order By: Relevance
“…Their assessments show that accounting for measurement and model errors in the assimilation greatly increases the precision of the tropospheric ozone over other methods of obtaining gridded TCO fields. Both Wargan et al (2015) and Ziemke et al (2014) show that there is greater disagreement of the tropospheric ozone analyses with sondes at high latitudes. For this reason, we restrict our discussion in the present study to the tropics and middle latitudes.…”
Section: Ozone Data and Geos-5 Data Assimilation Systemmentioning
confidence: 98%
See 2 more Smart Citations
“…Their assessments show that accounting for measurement and model errors in the assimilation greatly increases the precision of the tropospheric ozone over other methods of obtaining gridded TCO fields. Both Wargan et al (2015) and Ziemke et al (2014) show that there is greater disagreement of the tropospheric ozone analyses with sondes at high latitudes. For this reason, we restrict our discussion in the present study to the tropics and middle latitudes.…”
Section: Ozone Data and Geos-5 Data Assimilation Systemmentioning
confidence: 98%
“…Wargan et al (2015) provides more details on the OMI tropospheric sensitivity and the retrieval "efficiency factors", or averaging kernels, used in the assimilation. Wargan et al (2015) and Ziemke et al (2014) previously evaluated these ozone analyses relative to sondes and other satellite data. Their assessments show that accounting for measurement and model errors in the assimilation greatly increases the precision of the tropospheric ozone over other methods of obtaining gridded TCO fields.…”
Section: Ozone Data and Geos-5 Data Assimilation Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Fig. 12 of Ziemke et al (2014) showed that the assimilation product when limited to tropical latitudes had zonal variability ∼ 10-15 DU in stratospheric column ozone which was considerably larger than direct satellite measurements that typically have zonal variability of only a few DU. In addition, this larger zonal variability in stratospheric column ozone coincided with a reduced zonal wave-one pattern of TCO with assimilation, also considered inconsistent with previous TCO measurements.…”
Section: Data and Modelsmentioning
confidence: 89%
“…This method subtracts MLS stratospheric column ozone from OMI total column ozone for near clear-sky scenes (i.e., radiative cloud fractions < 30 %). Ziemke et al (2014) evaluated three other OMI/MLS TCO products and concluded that the Global Modeling and Assimilation Office (GMAO) data assimilation product was best to use overall when considering all factors including global coverage and ozone profile information. However, Fig.…”
Section: Data and Modelsmentioning
confidence: 99%